Influence of the molybdenum on characteristics of oxide films produced by micro-arc oxidation on Ti-15Zr-based alloys - Costa, N. A. [UNESP]; Correa, D. R.N.; Lisboa-Filho, P. N. [UNESP]; Sousa, T. S.P. [UNESP]; Grandini, C. R. [UNESP]; Rocha, L. A. [UNESP] (Elsevier, 2021)
Micro-arc oxidation (MAO) is a powerful tool to modify the surface of Ti alloys, in order to increase the lifetime of orthopedic implants. It is well established that the resulting oxide films are dependent on the parameters used during anodic treatment, however the influence of the substrate (bulk properties) is still a subject lacking for better understanding. This paper aims at studying the effect of molybdenum on characteristics of MAO films grown on promising Ti-15Zr-xMo alloys. The substrates were produced by arc-melting, and it was found to be constituted by α’ phase (Ti[sbnd]15Zr), α” + β phases (Ti-15Zr-5Mo), and only β phase (Ti-15Zr-10Mo and Ti-15Zr-15Mo). This β-stabilizing action of Mo was accompanied by modifications from lamellar to granular microstructures in the as-cast samples. After MAO treatment, Ti alloys containing Mo exhibited thinner oxide coatings with porous structures of smaller dimensions compared to the ones formed on Ti[sbnd]15Zr alloy, although the average pore shape has not been altered significantly. That film differences may be a result of changes in dielectric breakdown of the oxide through the formation of β phase in the bulk, while lamellar microstructures were also suppressed. Mo oxides (MoO3) were barely detected in the coatings, which were preferentially composed of TiO2 (anatase and rutile) and ZrO2. Regardless of the Mo content in the bulk, the coatings also showed CaCO3 and calcium phosphate compounds, indicating a successful incorporation of bioactive ions during MAO.
Keywords: Anodic oxide characteristics; Biomaterial; Bulk properties; Micro-arc oxidation; Ti-Zr-Mo alloy